Detecção precoce de recidivas em pacientes com mieloma múltiplo através da análise de imunoglobulinas monoclonais - Aita, Marta Helena Carlesso (2014)
Multiple myeloma (MM) is an incurable progressive hematologic malignancy with heterogeneous evolution. It is a disease characterized by abnormal clonal proliferation of plasma cells in the bone marrow producing monoclonal immunoglobulins and causing a number of organ dysfunctions. Most patients relapse after treatment. Therefore, the use of methods of analysis of serum and urinary samples in order to detect as early as possible the presence of monoclonal immunoglobulins, before the occurrence of relapses, may aid in the treatment of patients with MM, improving its quality and prolonging survival. In this study we compared the effectiveness of the techniques of immunofixation (IF) and electrophoresis (EP) in the detection of MM relapses. For this, 52 patients under treatment in the University Hospital of Santa Maria (HUSM) were monitored, being detected the relapse of the disease in nine of these patients. A retrospective analysis of serum proteins of the nine patients, between January 2012 and July 2014, showed that IF was more effective than EP in early detection of relapse, regardless of the present class of immunoglobulins. The precocity of IF in relation to EP in detecting MM relapses in the nine patients studied, ranged from 2.0 to 18.8 months, with a mean of 6.6 months. Thus, we suggest the implementation of IF in the Clinical Analysis Laboratory (CAL) of HUSM to help onco-hematology physicians in the diagnosis and supportive care for patients with MM.